Obra Des/Construída. Revisita a meia dúzia de lugares e projectos - Luís Filipe Morais Ricardo (2020)
The presented work re-visits a selection of built projects that evolved my contribution, over the last decade. Starting out as an intern in the Spanish office RCR Arquitectes, followed by a full-time employment in this office and afterwards taking a look at projects across Portugal, Germany and China, where I co-founded llLab with my partner Hanxiao Liu. Seeing with a watchful eye, understanding and feeling architecture takes time. This time gives us the opportunity to learn and understand. Therefore my professional timeline was used to subdivide this document into 5 sections. Hence, giving it structure, starting with present day projects in a reverse chronological order. Being aware that direct and first-hand experience is the best way to transmit information about a building, a flexible language is extremely important to convey the project information. Therefore, the use of graphical elements like drawings and photographs need to carefully balance written information. Human geography and physical geography are two core subjects, guiding us across others like intuition, preference, teamwork, culture, references and sustainability. With this awareness it is important to constantly analyze and critique relevant projects and theories. Something that accompanies us throughout our professional lives. Through these texts I try to create ideas from built works, rather than theorize about something I have never witnessed. Consequently, the true joy of architecture requires training, built from experiences and studies.